A scaling relation for the molecular cloud lifetime in Milky Way-like galaxies. Issue 2 (7th May 2021) - Jeffreson, Sarah M R; Keller, Benjamin W; Winter, Andrew J; Chevance, Mélanie; Kruijssen, J M Diederik; Krumholz, Mark R; Fujimoto, Yusuke
ABSTRACT: We study the time evolution of molecular clouds across three Milky Way-like isolated disc galaxy simulations at a temporal resolution of 1 Myr and at a range of spatial resolutions spanning two orders of magnitude in spatial scale from ∼10 pc up to ∼1 kpc. The cloud evolution networks generated at the highest spatial resolution contain a cumulative total of ∼80 000 separate molecular clouds in different galactic–dynamical environments. We find that clouds undergo mergers at a rate proportional to the crossing time between their centroids, but that their physical properties are largely insensitive to these interactions. Below the gas–disc scale height, the cloud lifetime τlife obeys a scaling relation of the form τlife ∝ℓ −0.3 with the cloud size ℓ, consistent with over-densities that collapse, form stars, and are dispersed by stellar feedback. Above the disc scale height, these self-gravitating regions are no longer resolved, so the scaling relation flattens to a constant value of ∼13 Myr, consistent with the turbulent crossing time of the gas disc, as observed in nearby disc galaxies.